Mediation of Jobsatisfaction, Knowledge Sharing, Organizasional Citizenship Behavior, And Performance Employee Privat Hospitals In Ambon City - Agusthina Risambessy; Pieter Novry Ruddy Rehatta; Saleh Tutupoho (Institute of Computer Science (IOCS), 2022)
The development of an increasingly changing era requires knowledge of change itself. In the world of work, knowledge of work is needed, not closing the possibility, but this possibility continues that the life of the world of work requires knowledge and to complete work quickly and precisely. So that knowledge sharing has an important role for nursing paramedics in hospitals. This study aims to develop mediation of job satisfaction, knowledge sharing, organizational citizenship behavior and employee performance. The unit of analysis studied was a private hospital in Ambon city, with the respondents being nursing paramedics. The sampling technique is purposive sampling where nursing paramedics have worked for more than 2 years. The analytical method used is PLS with Software Program SmartPLS vs 3.0. The results of the study prove that there is a positive and significant effect of knowledge sharing on employee performance, organizational citizenship behavior has a significant positive effect on employee performance. there is a positive and significant effect of knowledge sharing on employee performance mediated by job satisfaction, organizational citizenship behavior has a significant positive effect on employee performance mediated by job satisfaction. Job satisfaction has no significant effect on employee performance. Suggestions for further research can continue this study by developing deviant behavior in service practice in hospitals.